In Silico Design And Constant-Ph Molecular Dynamics Study Of Human Igg1 Fc At Ph6.0 And Ph 7.5 - Lim, Yee Ying (2020)
The use of monoclonal antibody against various illnesses such as cancer, infectious diseases or autoimmune disorders has become a mainstream in the field of medical therapeutics. Specifically, the IgG1 with long serum half-life has led to its popular usage as a therapeutic drug scaffold where this property is related to the pH-dependent binding mechanism of IgG1 with FcRn. In this work, constant pH molecular dynamics (CpHMD) simulation setup was first established by testing against experimentally validated Fc-FcRn complex (Wildtype, MutAAA and MutYTE), associating and dissociating at pH 6.0 and pH 7.5, respectively. Binding free energy (ΔGBind) calculation via the MMGBSA approach was used to describe the binding affinity for the control complexes (Wildtype-, MutAAA- and MutYTE-FcRn) and have showed Fc variant MutYTE as the strongest FcRn binder at pH 6.0. To obtain alternative Fc design with better binding properties for FcRn, pH 6.0 single trajectory MutYTE-FcRn representing complex was extracted by MMTSB toolset clustering followed by SAAMBE server single point mutations imposed on the MutYTE Fc of the complex. Mutagenesis result suggested four Fc positions with improved binding energy (ΔG) for FcRn. They were all applied to maximize the binding effect for FcRn, resulting the new IgG1 Fc variant design, MutM4 (Asp294Ala/Thr254Phe/Pro257Trp/ Asp312Gly).